Association and application in XDR and MR data - Tao LIU; Tao WU; Bin WANG (Dianxin kexue)
Based on the XDR and MR data records of O domain and combining with the development and practice in big data and machine learning technologies,the analysis of impact factors of correlation rate and accuracy was described in detail via practice with the help of technology of association of XDR and MR data records.By means of the integration of machine learning technology and fingerprint localization algorithm,the position accuracy was promoted constantly using the random forest algorithm,and the rasterization of associated data was realized.Simultaneously,the innovative application scenarios and directions applied to planning,network,customer and market were proposed.Finally,to verify the prospect of the association of XDR and MR data records,two examples in network construction,maintain and market were enumerated.